Economic Feasibility of Floating Cultivation System on Swampland - Desri Yesi; Tili Karenina; Wenni Tania Defriyanti; Achmad Ubaidillah (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2023)
Swampland is one of the agroecosystems that has not been optimally utilized, especially in agriculture. This land is included in sub obtimal land in South Sumatera province. This research aims to determine the feasibility of horticulture cultivation efforts with floating methods on swampland. The location of the research was the swampland in Srimulya Village, Sematang Borang District of Palembang City on inundated season from January to June. This study was conducted by combining interview methods and participatory observation with respondents. The method used in determining economic feasibility was business feasibility analysis using R/C and B/C Ratios. The types of data processed were primary data and secondary data with quantitative type. Based on the results, it can be concluded that floating cultivation system for kale can add family income to swampland. With the total cost of each harvest being Rp 4.390.000,00 , an acceptance of Rp 14.000.000,00 is obtained. The net income earned every harvest is Rp 9.610.000,00. The Revenue / Cost Ratio is 3.19 while Benefit / Cost Ratio is 2.19. It can be concluded that the floating cultivation system is feasible to be implemented on swampland.